2008
DOI: 10.1159/000163592
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Effect of ACE I/D and AGT M235T Polymorphisms on the Progression of Urinary Albumin Excretion in Taiwanese with Type 2 Diabetes

Abstract: Background: We investigated the gender differences in the effect of ACE I/D and AGT M235T polymorphisms on the prognosis of diabetic nephropathy (DN). Methods: A total of 525 type 2 diabetics were enrolled to participate in this prospective observational study. ACE and AGT gene polymorphisms were analyzed by polymerase chain reaction. The progression of DN was defined as a shift to a higher stage of DN or a doubling of the baseline serum creatinine level by the end of the study. Results: The baseline biophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
3
18
0
1
Order By: Relevance
“…They proposed that TT genotype by itself was not enough to increase the risk of renal dysfunction and that the high blood pressure may have contributed to the renal progression. However, others reported that AGT genotype was not associated with the progression of diabetic nephropathy in either gender [30]. In present study, the development of hypertension during follow-up was similar between the different genotypes in either gender.…”
Section: Discussionsupporting
confidence: 54%
“…They proposed that TT genotype by itself was not enough to increase the risk of renal dysfunction and that the high blood pressure may have contributed to the renal progression. However, others reported that AGT genotype was not associated with the progression of diabetic nephropathy in either gender [30]. In present study, the development of hypertension during follow-up was similar between the different genotypes in either gender.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we suggest that the genetic variation at the ACE locus as D/D variant in intron 16, contribute to an increased risk of nephropathy in T2DM patients, but not extent of DN severity (as the allelic or genotypic distribution was comparable between the two DN groups) in studied population. Our findings were in conformity with other studies [26][27][28][29][30][31] but not all [32,55,56]. This difference may possibly be due to different races, methods of quantitation and patient selection; as proteinuria in adults is a multifactorial condition frequently linked with diabetes, the issue of whether proteinuria is due to diabetes or some other etiology remains debatable, but there was no uncertainty in our group of patients on the role of T2DM in diabetic nephropathy constitution as we excluded the patients who had proteinuria/renal disorders before their diabetes was diagnosed, thus we confined our study to diabetic kidney diseases.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the contribution of ACE gene polymorphism to the heritable part of risk for diabetic nephropathy seems important, and is supported by findings from published meta-analyses [28,62] along with other studies done among Indians [31,63], Japanese [29], French [64], Egyptian [65] and Taiwan [27] diabetic patients. However, our results do not coincide with studies done among Chinese [66], Tunisian [55], French [56], Turkish [34] and Iranian [67] diabetic cases.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Albuminuria, elevated blood pressure (BP), and metabolic abnormalities explain only 30–50% of the variation in the progression of DN [3,4]. Familial clustering of diabetes and ethnic variation of DN suggest that hereditary factors also play an important role [5,6]. …”
Section: Introductionmentioning
confidence: 99%